2-{ 2-(Piperazin-4-ium-1-yl)ethyliminio methyl}phenolate 0.06-chloride 0.94-perchlorate - Reisi, M.R.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2011)
The structure of the title salt, C13H20N3O+center dot 0.94ClO(4)(-)center dot 0.06Cl(-), contains a zwitterionic Schiff base with a net positive charge and a perchlorate anion having substitutional disorder with Cl. In the cation, the azomethine N atom is protonated and donates hydrogen bonds to the phenolate O atom and to the tertiary N atom of the piperazine ring. In the crystal, two Schiff base molecules are linked about a center of inversion by a pair of N-H center dot center dot center dot O hydrogen bonds. The resulting dimers are N-H center dot center dot center dot O and C-H center dot center dot center dot O hydrogen bonded to the perchlorate anions, forming a three-dimensional structure. The network is further consolidated by C-H center dot center dot center dot pi interactions.